The Selfishnessin the View of Thomas' Hobbes and Theravada Buddhist Philosophy - Prichadireak, Tinnakorn; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2022)
This academic paper aims to present Thomas' selfishness. Hobbes and Theravada Buddhist Philosophy as follows : 1) Unlike ; Thomas Hobbs, it is a political struggle that competes for interests and power, doing so is detrimental to the security of society. Hobbes used the law to solve social problems. Everyone had to adhere to the promises made to the people in order to achieve some degree of peace. As for Theravada Buddhist philosophy, emphasis is placed on development in order to lead a suitable way of life by emphasizing people in society with conscience and focusing on the benefits and happiness of the society. 2) Similarly; it was found that the ideas of Thomas Hobbs and Theravada Buddhist philosophy each had goals for the benefit of society. But there are different approaches. Hobbes sees the need to develop selfishness or harnessing selfishness to benefit. As for Buddhist philosophy, it aims to eliminate selfishness until the end.